A Simulation Based Study of Flow Velocities across Cross Flow Turbine at Different Nozzle Openings. (2016) - Chichkhede, Shashi; Verma, Vinay; Gaba, Vivek Kumar; Bhowmick, Shubhankar
Abstract: The present work reports CFD based investigation of the effect of design parameters on the flow velocities of a cross flow turbine (CFT). Best described as an impulse type turbine with partial admission of air, cross flow turbines meet the demand for an efficient turbine to run at low head that is also easy to manufacture. The design of cross–flow turbine is unique due to the generation of power during two stages. This type of turbine is often used in small hydropower plants located in less–developed countries. The design parameters of CFT that can be varied to increase overall efficiency and power output of the turbine are water inlet angle, blade angle at inlet and outlet. In the present work the design parameters are varied for different nozzle openings and simulated using CFD. A full 3-D steady state flow simulation of the cross-flow turbine is performed including casing, runner and nozzle assembly.